THE ROLE OF GOVERNMENT, TRADITIONAL INSTITUTION, AND SOCIAL CAPITAL FOR EMPOWERING SMALL AND MEDIUM INDUSTRIES - Ni Nyoman Yuliarmi; Agus Suman; S.M. Kiptiyah; Ahmad Erani Yustika (Universitas Hayam Wuruk Perbanas, 2012)
There are some factors which are deemed to have an effect in empowering the small and mediumindustries (SMIs). This study determines the roles of government, traditional institutions, and socialcapital for the empowerment of SMIs. Purposive Sampling method was used to determine the district/city in the sample. Sample units in each selected district/city were used Stratified RandomSampling method as many as 204 people. Structural Equation Modeling (SEM)-based variance isused as analysis technique aided by program Partial Least Square (PLS). The results showed that:1) the role of government through the relevant agencies has not been able to directly influence theempowerment of SMIs. 2) The role of traditional institutions through social roles, cultural, economicand financial has a positive effect for the empowerment of SMIs. 3) Social capital has a positiveeffect on the role of government to empower SMIs. 4) Social capital has a positive effect on therole of traditional institutions for the empowerment of SMIs. 5) Social capital is not directly affectingthe empowerment of SMIs. 6) The role of government through the relevant agencies has a positiveinfluence on the role of traditional institutions for the empowerment of SMIs.